Avaliação da eficácia dos biocurativos em ratos wistar com lesões de pele causadas por queimaduras - Abruceze, Leila Haddad Barrach; cotrim, Ondina Silvia; Pasian, Ana Carolina Picolo; Deffune, Elenice; Ferreira, Rosana Rossi [UNESP] (My University, 2014)
Accidents caused by thermal, chemical, electrical or radioactive agents cause skin lesions causing burns of varying degrees. The therapeutic approach aims to restore damaged tissues and involves a wide range of products on the market. This study aims to evaluate the use of biological dressing, biotech product developed at the Blood Center of Botucatu / UNESP obtained from fresh frozen plasma or platelet concentrate with in vitro addition of thrombin and calcium gluconate. This addition in the platelet concentrate, intended to release the active growth factors of the platelets granules on the healing process. The study of the effectiveness of Platelet Gel home made in Wistar rats was established, in agreement with scald burns, comparing efficacy and cost of Platelet Gel with usual hospital -based treatment collagenase + chloramphenicol plus cost analysis through pharmacoeconomics. We used 25 Wistar rats were divided into 3 treatment groups: Group A, Collagenase + Chloramphenicol; Group B, Platelet Gel and C, control. The products were applied every other day for 30 days in animals. In group A, there was the presence of erythema and crust in all animals. The exudates was indentified 2/10 animals. For the Group B, we observed the presence of erythema and crust at all and no presence of exudates. In group C all the animals showed erythema with no presence of exudates and scab occurred in 1/10. Statistical analysis showed significant difference ( p < 0.0 ) for crust formation between Groups B and C. In the histological analysis, group A showed a slight amount of blood vessels and collagen fibers, moderate amounts of macrophages and fibroblasts was observed while B and C groups showed moderate amounts of blood vessels, macrophages and fibroblasts and discreet presence of collagen fibers. The re-epithelialization occurred in most animals of all groups without significant statistical differences. For the aspects of pharmacoeconomics, the platelet gel presented a better cost - effectiveness in relation to treatment based on collagenase / chloramphenicol. In light of the ethical aspects of the raw material is the result of spontaneous blood donation, the proposal should have biological dressings productions the responsibility of public blood transfusion centers for free distribution. This may point to the production chain of Brazilian blood banks like special blood components for use no intravenous.

Acidentes por agentes térmicos, químicos, elétricos ou radioativos causam lesões de pele ocasionando queimaduras de diferentes graus. O tratamento destas lesões visa restaurar os tecidos lesados e envolve uma variada gama de produtos no mercado. Este trabalho se propõe a avaliar o uso dos biocurativos, produto biotecnológico desenvolvido no Hemocentro de Botucatu/UNESP obtidos a partir de plasma fresco congelado ou concentrado de plaquetas com adição in vitro de trombina e gluconato de cálcio. Esta adição, no Concentrado de Plaquetas, visa a liberação de fatores de crescimento atuantes no processo de cicatrização. O estudo da eficácia do Gel de Plaquetas home made em ratos Wistar foi estabelecido, em protocolo com queimaduras por escaldo, comparando eficácia e custo do Gel de Plaquetas com o tratamento hospitalar usual à base de colagenase+cloranfenicol além de análise de custo através da farmacoeconomia. Utilizou-se 25 ratos da raça Wistar, divididos em 3 grupos tratados: Grupo A, Colagenase+Cloranfenicol; Grupo B,Gel de Plaquetas e C,controle. Os produtos foram aplicados em dias alternados nos animais por 30 dias. No grupo A, observou-se eritema e presença de crosta em todos os animais. A presença de exsudato ocorreu em 2/10 animais. No grupo B, observou-se presença de eritema e crosta em todos e não houve exsudato. No grupo C, todos apresentaram eritema, com ausência de exsudato e a presença de crosta ocorreu em 1/10. Na analise estatística foi observada diferença significativa (p < 0,0) para formação de crosta entre os Grupos B e C. Na análise histológica, o grupo A apresentou discreta quantidade de vasos sanguíneos e fibras colágenas, quantidades moderadas de macrófagos e fibroblastos enquanto que os grupos B e C apresentaram quantidades moderadas de vasos sanguíneos, macrófagos e fibroblastos e discreta presença de fibras colágenas. A reepitelização ocorreu na maioria dos animais de todos os grupos sem diferença significativa. Quanto aos aspectos de farmacoeconomia, o gel de plaquetas apresentou melhor custo-efetividade em relação ao tratamento à base de colagenase/cloranfenicol. Tendo em vista de que a matéria prima utilizada é fruto de doação de sangue espontânea, os biocurativos devem ter proposta de produção nos laboratórios públicos para distribuição gratuita podendo apontar para a produção pela cadeia dos hemocentros brasileiros, como hemocomponentes especial.
Evaluating the effectiveness of biocurativos in rats with skin lesions caused by burns
Keywords: Burns; Platelet; Collagenase; Biological dressings; Queimaduras; Plaquetas; Colagenase; Curativos biológicos